Treatment of juvenile chronic granulocytic leukemia - Hiçsönmez, Gönül; Zamani, Vahide (The Turkish Journal of Pediatrics, 1982)
A 9-month-old boy with juvenile chronic granulocytic leukemia was treated with cytosine arabinoside and 6-mercaptopurine. Although in these patients the median survival time is very short, our patient has survived for 48 months since the diagnosis and is still free of disease. Since effective treatment still remains a problem in JCGL, our protocol of treatment seems to be promising.